2009
DOI: 10.1002/ejoc.200900689
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on Tautomerism of Dihydro‐2H‐1,5‐benzodiazepin‐2‐ones and Dihydro‐2H‐1,5‐benzodiazepine‐2‐thiones

Abstract: DFT calculations were performed to study the tautomeric rearrangements in the isolated, monoethanol-and diethanolsolvated, and dimeric forms of 4-methyl-1,3-dihydro-2H-1,5-benzodiazepin-2-one and 4-methyl-1,3-dihydro-2H-1,5-benzodiazepine-2-thione. Molecular geometries of the tautomers and transition state structures were optimized at the B3LYP/6-31G(d) and B3LYP/6-311++G(d,p) levels of theory. The long-range solvent effects on the geometrical and energy parameters of tautomerization were also analyzed by use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…Our results agree with those of Okovytyy et al [14] now including 3e : 3a (0.0) > 3b (14.7) > 3d (48.6) > 3e (64.0) > 3c (96.5). For the remaining compounds always is a (0.0) > b (18 kJ mol −1 in average), the other tautomers having considerably higher energies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with those of Okovytyy et al [14] now including 3e : 3a (0.0) > 3b (14.7) > 3d (48.6) > 3e (64.0) > 3c (96.5). For the remaining compounds always is a (0.0) > b (18 kJ mol −1 in average), the other tautomers having considerably higher energies.…”
Section: Resultssupporting
confidence: 93%
“…A comprehensive theoretical study of the tautomerism of 3 was carried out by Okovytyy et al in 2010, including monoethanol and diethanol solvates as well as dimeric forms [14] (they do not consider tautomer 3e ). In the gas phase their relative energies (in kJ mol −1 ) are: 3a (0.0) > 3b (14.6) > 3d (48.5) > 3c (93.4) and with an ethanol molecule they are: 3a (0.0) > 3b (0.6) > 3d (51.3) > 3c (70.0).…”
Section: Resultsmentioning
confidence: 99%
“…Although it was possible to converge this calculation, it did not yield a single-proton TS. These findings are in agreement with previous studies on the mechanism of the keto-enol tautomerism of nucleic acid bases, [19,[44][45][46] pyridine derivatives, [38][39][40][41] and other compounds [43,51] in aqueous media. It was found that the tautomerization reactions proceed preferentially by a multiple proton-transfer mechanism with the assistance of two to three water molecules.…”
Section: Calculationssupporting
confidence: 94%
“…For instance, the migration of the hydrogen atom to the nitrogen atoms in both the imidazole and the tetrazole rings can lead to the tautomeric forms. This is well rationalized with the earlier study on the prototropic tautomerism [31][32][33] through the migration of the hydrogen atom in both the imidazole [34][35][36] and the tetrazole rings [37][38][39].…”
Section: Introductionmentioning
confidence: 70%